Numerical and experimental analysis on motion performance of new sandglass-type floating body in waves. (March 2016) - Wang, Wen-hua; Wang, Lin-lin; Du, Ya-zhen; Yao, Yu-xin; Huang, Yi
Abstract: In order to solve the performance limitations of traditional ship-type and cylindrical FPSO, this paper presents a new concept of sandglass-type FPSO. For the new sandglass-type floating model, firstly by using classic boundary element method based on wave potential theory, the effects of shape parameters on motion performance of sandglass-type model are studied. Then the wave frequency versus minimum heave motion RAO is selected as the critical design parameter to control heave motion of new floating model, and its convenient engineering estimation expression is theoretically and mathematically deduced. Furthermore, on this basis the design guideline for sandglass shape is analyzed and proposed. Next according to the information of a cylindrical FPSO, a sandglass-type floating model with the same basic function has been designed. Finally, by analyzing the numerical solution and experimental data, the numerical boundary element method and design guideline in this paper can be validated to be effective and accurate. Furthermore, it can be found that the sandglass-type design can obviously improve the hydrodynamic performance of FPSO. Thus this paper can provide an innovative engineering platform and a design proposal for the development of ocean oil and gas exploitation. Highlights: A new FPSO with sandglass-type floating body is proposed. Particular design guideline for new model is theoretically deduced. Shape design of new model can greatly improve heave motion performance.